Rodolfo Garcia outlined in letters: Tensions between the erudite and intellectual - Broenstrup, Gabriela D'Avila [UNESP] (Univ Federal Ouro Preto, Dept Historia, 2017)
The demands a person handles on letters over his crafts enable the analysis of the roles this person assumes and the building of his personal image. This paper deals with some queries that were asked to Rodolfo Augusto de Amorim Garcia (1873-1949), an autodidact who produced history during 1930s and 1940s through letters to his pairs. The different manners Garcia is identified - sometimes erudite, sometimes intellectual - raised some questions: What were the activities the so-called erudites carried out? What reasons led some of them to call Garcia an intellectual? What contribution could be assigned to him on the so-called essayistic tradition that emerged in Brazil during the first half of the 20th century? Such reflections will guide the research on the use of knowledge in a period of investments on professional training and of shaping a new model of historians in Brazil.
Keywords: Historian; Erudition; Intellectual